Contributions of Iranian Journal of Medical Sciences (IJMS) during the COVID-19 Pandemic - Ali Akbar Asadi-Pooya (Shiraz University of Medical Sciences, 2021)
Since late 2019, the world and since early 2020, Iran has been experiencing a catastrophic pandemic of the coronavirus disease 2019 (COVID-19), which is caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2).1 This fatal virus has a high potential for person-to-person transmission; therefore, this deadly outbreak has caused massive job losses, various psychiatric problems, and increasing difficulties for all businesses worldwide.2-5 Production of scientific data and its timely dissemination are the essential elements of an effective response to any crisis including the current pandemic. The current study aimed to determine the early contributions of the Iranian Journal of Medical Sciences (IJMS) during the COVID-19 pandemic in 2020. We retrieved all the IJMS publications in 2020 and divided the published articles into three main categories: clinical sciences, basic sciences, and editorials. We also identified and highlighted the studies related to COVID-19.